2013
DOI: 10.1128/jvi.01234-13
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein Kinase A Regulation of the E6 PDZ-Binding Domain during the Differentiation-Dependent Life Cycle of Human Papillomavirus Type 18

Abstract: Human papillomavirus (HPV) E6 proteins of high-risk alpha types target a select group of PSD95/DLG1/ZO1 (PDZ) domain-containing proteins by using a C-terminal PDZ-binding motif (PBM), an interaction that can be negatively regulated by phosphorylation of the E6 PBM by protein kinase A (PKA). Here, we have mutated the canonical PKA recognition motif that partially overlaps with the E6 PBM in the HPV18 genome (E6153PKA) and compared the effect of this mutation on the HPVl8 life cycle in primary keratinocytes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
84
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 42 publications
7
84
0
1
Order By: Relevance
“…It is unclear from our experiments whether HPV-16_E6⌬PBM genomes are lost immediately or progressively during cell passaging, but this has been addressed in a recent publication from the Roberts laboratory, which demonstrated that HPV-18 genomes where PBM is deleted from E6 are maintained episomally in early passage transfected keratinocytes, but progressively lost upon cell passaging (37). It is also possible that there could be differences in outcome had our experiments been conducted in primary keratinocytes instead of NIKS cells, where HPV oncogene expression is not necessary for NIKS immortalization.…”
mentioning
confidence: 61%
“…It is unclear from our experiments whether HPV-16_E6⌬PBM genomes are lost immediately or progressively during cell passaging, but this has been addressed in a recent publication from the Roberts laboratory, which demonstrated that HPV-18 genomes where PBM is deleted from E6 are maintained episomally in early passage transfected keratinocytes, but progressively lost upon cell passaging (37). It is also possible that there could be differences in outcome had our experiments been conducted in primary keratinocytes instead of NIKS cells, where HPV oncogene expression is not necessary for NIKS immortalization.…”
mentioning
confidence: 61%
“…HR HPV, which is considered to be a necessary biological factor for CC, can express specific viral genes such as E6 and E7, which have been observed in CC cell lines and biopsies (4,5). These specific viral genes express oncoproteins (such as E6 and E7 proteins) that can be inserted into the host's cell genome (6).…”
Section: Introductionmentioning
confidence: 99%
“…The E6 oncoproteins of high-risk HPV types have a C-terminal PDZ-binding motif (PBM) that is important for a normal viral life cycle and progeny production (for a review, see reference 3). PBM deletion causes viral genome integration, loss of replicative competence, and an increased potential for oncogenic transformation (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%